Water quality and phytoplankton structure and functional classification in Tadlac Lake, Philippines - MARY SHEENALYN P. RODIL; CLARISSE BANAAG; ELIJAH JAYRALD T. VELASCO; ERWIN P. ELAZEGUI (Society for Indonesian Biodiversity, 2024)
Abstract. Rodil MSP, Banaag C, Velasco EJT, Elazegui EP. 2024. Water quality and phytoplankton structure and functional classification in Tadlac Lake, Philippines. Biodiversitas 25: 2769-2782. Following the ban on aquaculture enforced from December 1999 to February 2000, the local government of Tadlac Lake, Philippines, is currently developing ecotourism projects in the lake. This necessitates the assessment of water quality and phytoplankton to ensure the sustainability of the lake, supporting both ecological preservation and visitor satisfaction. This present study unveils the current ecological condition of Tadlac Lake, while advancing knowledge of phytoplankton's responses to different environmental conditions and adaptation mechanisms through their functional classifications. Our study revealed that except for phosphate during the dry period, water quality parameters adhered to the standards for class C waters. Phytoplankton species are grouped into Phaeophyta, Cyanobacteria, and Chlorophyta. Bacillariophyceae was the most dominant class with 15 species. The persistent presence of Stephanodiscus hantzschii, Synedra affinis, Synedra tabulata, Achnanthes lanceolata, Navicula placentula, Neidium affine, Synechocystis aquatilis, Oscillatoria limosa, and Chlorococcum humicola indicate that the lake's recovery from past deterioration remains incomplete. Shannon-Weiner and Pielou evenness index suggested that the lake exhibits a state of light pollution. The Wilcoxon signed rank test reveals significant seasonal variations in environmental factors, including temperature, total dissolved solids, salinity, electrical conductivity, pH, dissolved oxygen, phosphates, and total coliform counts, which directly impact the structure and functional classification of phytoplankton communities. Spearman correlation coefficients and canonical correspondence analysis further establish significant correlations between individual phytoplankton species and these environmental parameters, providing additional evidence. The results emphasize the need for seasonally tailored environmental management strategies.